Contesting images of gender: reexamining Mizoguchi Kenji's Sisters of the Gion for the twenty-first century. Issue 1 (2nd January 2017) - Hansen, Kelly
ABSTRACT: Japan today is known for one of the lowest levels of gender equality in the developed world. Orientalist perceptions of feminine beauty, both domestically and internationally, frequently contribute to this gender gap by privileging nostalgic images of women who conform to premodern values. This study examines Mizoguchi Kenji's well-known 1936 film Sisters of the Gion ( Gion no shimai ), a work that has gained a new audience in the twenty-first century through release on DVD. I propose that re-examining this film as a loose adaptation of Aleksandr Kuprin's portrayal of prostitution in his early twentieth- century Russian novel Yama: The Pit (1909–1915) can expose these contesting images of nostalgia and gender inequality. Centered on the geisha world of the 1930s, Sisters of the Gion depicts the struggles faced by women whose existence depends on the whims of men. When considered alongside Yama, the film becomes not simply a depiction of an outdated geisha system, but a broader statement of the inability of women to attain any degree of autonomy in a world where premodern patriarchal values continue to govern social norms.